History and development in Uzbek animated films (Texas Journal of Multidisciplinary Studies, 2023)
The topic of this article is related to tradition and innovation in Uzbek animated films, it is important to assess the place of animation in civilization processes as much as possible, to analyze the stages of development of Uzbek animation art, scientific creative research and its prospects in a scientific manner. Today, several problems can be solved by analyzing the process of creating animated films. Undoubtedly, this topical research paper will be useful for future artists and filmmakers.